Bobshannonite, Na2KBa(Mn, Na)8(Nb, Ti)4(Si2O7)4O4(OH)4(O, F)2, a new TS-block mineral from Mont Saint-Hilaire, Québec, Canada: Description and crystal structure. (1st December 2015) - Sokolova, E.; Cámara, F.; Abdu, Y.A.; Hawthorne, F.C.; Horváth, L.; Pfenninger-Horváth, E.
Bobshannonite, Na2KBa(Mn, Na)8(Nb, Ti)4(Si2O7)4O4(OH)4(O, F)2, is a new TS-block mineral from Mont Saint-Hilaire, Québec, Canada. It occurs as blocky crystals 0.5–1 mm across, perched on sérandite and albite. Other associated minerals are epididymite, catapleiite, aegirine, kupletskite, rhodochrosite and rhabdophane-(Ce). Bobshannonite occurs as vitreous to frosty, transparent to translucent very pale brown to orange brown crystals, has a very pale brown streak, hackly fracture and does not fluoresce under cathode or ultraviolet light. Cleavage is 001 very good, no parting was observed, Mohs hardness is ∼4, it is brittle and Dcalc. = 3.787 g/cm3. Crystals are twinned extensively and do not extinguish in cross-polarized light. Bobshannonite is triclinic, C1, a = 10.839(6), b = 13.912(8), c = 20.98(1) Å, α = 89.99(1), β = 95.05(2), γ = 89.998(9)°, V = 3152(5) Å3. The six strongest reflections in the powder X-ray diffraction data [d (Å), I, (hkl)] are: 2.873, 100, (241, 241, 044, 044, 241, 241); 3.477, 60, (006); 3.193, 59, (224, 224); 2.648, 40, (402, 243, 243); 2.608, 35, (008, 226, 226); 1.776, 30, (249). Chemical analysis by electron microprobe gave Ta2O5 0.52, Nb2O5 19.69, TiO2 5.50, SiO2 26.31, Al2O3 0.06, BaO 7.92, ZnO 1.02, FeO 0.89, MnO 26.34, MgO 0.06, Rb2O 0.42, K2O 2.38, Na2O 4.05, F 0.70, H2Ocalc. 1.96, O = –0.29, total 97.53 wt.%, where the H2O content was calculated from the crystal-structure analysis. The empirical formula on the basis of 38 anions is Na1.89(K0.93Rb0.08)Σ1.01Ba0.95(Mn6.85Na0.52Zn0.23Fe0.232+Mg0.03Al0.02)Σ7.88(Nb2.73Ti1.27Ta0.04)Σ4.04(Si8.07O28)O9.32H4.01F0.68, Z = 4. The crystal structure was refined to R1 = 2.55% on the basis of 7277 unique reflections [F > 4σ(F)] and can be described as a combination of a TS (Titanium Silicate) block and an I (Intermediate) block. The TS block consists of HOH sheets (H – heteropolyhedral, O – octahedral). The topology of the TS block is as in Group II of the Ti disilicates: Ti + Nb = 2 a.p.f.u. per (Si2O7)2 [as defined by Sokolova (2006)]. In the O sheet, ten [6]MO sites are occupied mainly by Mn, less Na and minor Zn, Fe2+, Mg and Al, with = 2.223 Å. In the H sheet, four [6]MH sites are occupied by Nb and Ti (Nb > Ti), with = 1.975 Å, and eight [4]Si sites are occupied by Si, with = 1.625 Å. The MH octahedra and Si2O7 groups constitute the H sheet. The TS blocks link via common vertices of MH octahedra. In the I block, Ba and K are ordered at the AP(1) and AP(2) sites with Ba:K = 1:1 and the two BP sites are occupied by Na. The ideal composition of the I block is Na2KBa a.p.f.u. Bobshannonite, perraultite, surkhobite and jinshajiangite are topologically identical Group-II TS-block minerals. Bobshannonite is the Nb-analogue of perraultite. The mineral is named bobshannonite after Dr. Robert (Bob) D. Shannon (b. 1935), in recognition of his major contributions to the field of crystal chemistry in particular and mineralogy in general through his development of accurate and comprehensive ionic radii and his work on dielectric properties of minerals.